A sexualidade de um sujeito que vive com esclerose múltipla - Cukier, Patrícia (2021)
Objective: The present dissertation aims to analyze the sexuality of a subject who lives with multiple sclerosis and its multiplicities, based on the premises of socio-historical psychology. Method: It was a total of 32 sessions of individual psychotherapy, however, due to the difficulty of locomotion of the querent, online platforms were used. The sessions that took place weekly and were transcribed live by the therapist. We use the dialectical materialist method, due to its capacity to produce reflections, to build its own meanings in relation to issues related to sexuality. The collected data allowed a qualitative analysis of the indicators and thematic content presented by the subject. Result: The consultant was able to consider his interpersonal, intrapersonal, marital relationships, his bodily limits, traumas of violence and his action potentials in the face of the challenges of MS itself, identifying the different territories that cross his sexuality. Conclusion: The subjectification process cannot be considered merely cognitive and biological, disregarding the subject's complexities and multiplicities, resulting from socio-historical conditions that emerge in specific contexts. The development of the subject's potential can help in the construction of new narratives, confrontations, affective and sexual experiences, capable of producing unique senses and meanings. We need to open space to consider the social, subjective and cultural dimensions that permeate sexuality, so that we can understand how we perceive reality and the possibilities of existence that inhabit our active and constant mind and body. The debate on sexuality within the clinic of socio-historical psychology is capable of promoting a better quality of life in individuals living with multiple sclerosis